A case of Ustilago spp. infection identified by whole genome sequencing in a pediatric patient undergoing open-chest extracorporeal membrane oxygenation - Valeria Fox; Gianluca Vrenna; Gianluca Foglietta; Luna Colagrossi; Barbara Lucignano; Manuela Onori; Venere Cortazzo; Marilena Agosta; Martina Rossitto; Maria del Carmen Pereyra Boza; Vanessa Fini; Annarita Granaglia; et al. (International Journal of Infectious Diseases)
Objectives: Patients undergoing extracorporeal membrane oxygenation (ECMO) are susceptible to fungal infections, also from rare or emerging pathogens. We present a case of a 3-year-old male patient hospitalized for respiratory failure and subjected to open-chest ECMO support, with a fungal infection from a pathogen not identifiable by standard methods. Methods: Although T2Candida panel (T2 Biosystems) resulted negative, blood cultures resulted positive for fungi after 4 days, confirmed by Gram staining. The fungus underwent typing using Bruker matrix-assisted laser desorption ionization-time of flight mass spectrometry system and Autobio Autof ms1000, which could not precisely identify the microorganism. Ultimately, whole genome sequencing (WGS) was performed directly on blood culture. Results: WGS analysis revealed in 5 days the presence of a fungus belonging to the Ustilago genus, a group of fungi commonly found in the environment but rarely causing human diseases. Conclusions: To the best of our knowledge, we presented the first case of an Ustilago spp infection in a pediatric patient undergoing ECMO, not identified by standard techniques but only by WGS performed directly on a blood sample in 5 days. Despite the paucity of literature on Ustilago spp infections treatment, therapy adjustments led to the eradication of the pathogen, underscoring the importance of advanced molecular techniques for the correct and timely identification of these microorganisms.